THE LEGAL PULSE OF NURSING: EVALUATING NURSES’ COMPETENCE IN HANDLING MEDICOLEGAL CASES - Rani, Smitha; Shetty, Suraj S; Niveditha, R Sai; M, Arun; HV, Chandrakanth (Journal of Forensic Medicine and Toxicology, 2025)
Introduction: In healthcare settings, Nurses occupy a pivotal role, not only in delivering patient care but also in ensuring medicolegal compliance. Understanding the legal framework and professional responsibilities of nurses in medicolegal cases is essential to providing high quality care while minimizing legal risks. This study aims at assessing and analyzing the knowledge and awareness about medicolegal issues among nurses. Materials and methods: A self-administered, structured questionnaire was used, and responses were obtained from Nurses who had recently graduated from a Nursing College located in South Karnataka. Questions about the identification of medicolegal issues, the medicolegal aspect of handling emergencies, and method of evidence collection were included in the survey. Response to each question was recorded and then analysed.
Keywords: Competency Assessment; Medicolegal Cases; Nursing Education